KETIKA BENCANA TERJADI: STUDI KASUS PENYELAMATAN DAN PEMULIHAN DOKUMEN MASYARAKAT - Riyadi, Aris (BACA: Jurnal Dokumentasi dan Informasi, 2018)
At the end of 2013, natural disaster Haiyan Cyclone suddenly struck Philippines destroying various infrastructures including representative of property identity assets such as community-owned land documents that stored at Tacloban municipal land administration office. This paper reviews recovery process and handling management of important documents damaged by water in depth and comprehensive. There are some lessons and challenges that can be taken in real time from the volunteer who go directly to help community. Knowledge applied using manual rescue stages and freeze dry vacuum technology adjusts to existing field conditions. For Indonesia it self, now is the time to build many disaster management facilities and experts which is known as multidisciplinary and advanced knowledge. From this lesson we can get a various things from field of information science and documentation. So that in the future four mains basic disaster management which are prevention, preparedness, response, and recovery can be applied by various elements of society.